Modeling of pressure control in a cryogenic tank by a thermodynamic vent system considering flash evaporation. (1st May 2023) - Qin, Xujin; Meng, Chuiju; Huang, Yonghua
Highlights: Flashing effect was considered into a tank that equipped a TVS for the first time. It is found that flash evaporation plays an important role in depressurization that is caused by TVS. Efficiency of the TVS was analyzed by proposing two non-dimensional parameters. Abstract: Thermodynamic vent system (TVS) has been recognized as a promising method for pressure control in cryogenic propellant tanks in microgravity environments. Prior simulations basically treated the liquid in the tanks quasi-static during the depressurization process via a venting operation. However, experimental evidence suggests that the liquid could be metastable and superheated at that moment. Therefore, improved models are needed for a more accurate simulation of the transient liquid-vapor phase change and heat transfer during the TVS depressurization. A new model that considers flash evaporation effect has been developed in the present work. The predicted pressure agrees with the experimental data better than those by conventional models. It is found that the flashing phenomenon plays a significant role in the depressurization, and behaves more intensely in the lower fill level cases. The flashing duration is mainly determined by the width of the pressure control band. The model has also been used to analyze the efficiency of the TVS in reducing propellant loss. It is found that the ineffectiveness of the heat exchanger and the unbalance of heating and cooling to the ullage in a full cycle are the main causes for the efficiency degradation of the TVS. Either increasing heat exchanging area, reducing orifice diameter of the throttling device or narrowing the pressure control band helps to improve the efficiency.